2022
DOI: 10.1177/02724316221078832
|View full text |Cite
|
Sign up to set email alerts
|

Early Adolescents’ Gender Typicality and Depressive Symptoms: The Moderating Role of Parental Acceptance

Abstract: In a school sample of early adolescents, we expanded the view of gender typicality to include adolescents who varied in the extent of felt similarity to own- and other-gender peers, and examined how their felt own- and other-gender similarity, are related to depression. Further, we examined the moderating role of parental acceptance of gender atypicality. Participants were 504 ethnically/racially diverse sixth graders ( Mage = 11 years, SD = 0.56, 51.6% boys) and their parents. Path analyses showed that adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…One possible explanation for these findings could be differences in how high and low SES individuals are socialized, such that high SES individuals might be socialized in environments that place a stronger emphasis on egalitarian values, or at least the social desirability of these egalitarian values (An, 2015). Indeed, parents can exercise a large influence on the gender development of children and adolescents (Xiao et al, 2022), and their general gender attitudes can impact those of adolescents. Some research has shown that stronger felt pressure to conform to gender norms coming from parents predicted more agreement with sexist remarks among children and preadolescents (Schroeder & Liben, 2020).…”
Section: Examination Of the Role Of Perceiver's Sesmentioning
confidence: 99%
“…One possible explanation for these findings could be differences in how high and low SES individuals are socialized, such that high SES individuals might be socialized in environments that place a stronger emphasis on egalitarian values, or at least the social desirability of these egalitarian values (An, 2015). Indeed, parents can exercise a large influence on the gender development of children and adolescents (Xiao et al, 2022), and their general gender attitudes can impact those of adolescents. Some research has shown that stronger felt pressure to conform to gender norms coming from parents predicted more agreement with sexist remarks among children and preadolescents (Schroeder & Liben, 2020).…”
Section: Examination Of the Role Of Perceiver's Sesmentioning
confidence: 99%
“…Replication of these results in similar contemporary populations may help resolve whether these results reflect recent changes in depressive symptom trajectories generally, or whether they are unique to this study population. Furthermore, although depression risk is known to vary across the full spectrum of gender expression, including increased prevalence among transgender and gender non-conforming youth, 36 38 our study data were limited to self-reported binary sex. Finally, our modeling approach assumed fixed variances within classes that may not fully capture the clinical heterogeneity of adolescent mental health experiences within trajectory classes.…”
Section: Discussionmentioning
confidence: 99%